Reliable Bulk-Data Dissemination in Delay Tolerant Networks - Zeng, Deze; Guo, Song; Hu, Jiankun (IEEE transactions on parallel and distributed systems, 2014)
Delay/Disruption Tolerant Network (DTN) differs from the conventional networks in that it has no continuous or contemporaneous connections among wireless nodes. Its inherent characteristic of intermittent connections makes existing routing solutions hardly to be applied directly. Epidemic routing using random linear network coding has been studied and proved as an efficient way for delivering small amount of data. To our best knowledge, we are the first to study high performance reliable transmission for bulk or stream-like data in DTNs. In this paper, we propose a dynamic segmented network coding scheme to efficiently exploit the transmission opportunity that is scarce in DTNs. In particular, we adopt a dynamic segment size control mechanism, which makes the segmentation adapt to the dynamics of the network. A lower bound of the expected delivery delay for bulk-data dissemination using segmented network coding is also derived. Both analytical and simulation results validate the high performance of our proposal. Several other interesting findings are also observed.